Arab Republic of Egypt : Cost Assessment of Environmental Degradation - World Bank (Washington, DC, 2013)
The report is a first step in a process towards the use of environmental damage cost assessments, for priority setting, and as an instrument for integrating environment, into economic, and social development. The report provides estimates of damage, and remediation cost for several areas of the environment, and, as areas of priority are identified, further analysis would be required for more accurate estimates. The damage cost of environmental degradation in Egypt in 1999, is estimated at 3.2-6.4 percent of GDP, with a mean estimate of 4.8 of GDP. In addition, the damage cost to the global environment is estimated at 0.6 percent of GDP. The cost of air pollution is assessed at 1.1-3.2 percent of GDP (urban outdoor and rural indoor), followed by soil degradation at 1.0-1.4 percent (erosion and salinity). In the area of water, the damage cost is estimated at 0.7-1.2 percent of GDP (mostly from the lack of safe water, sanitation and hygiene). Cost of coastal zone degradation is estimated at 0.2.-0.4 percent of GDP, and, inadequate waste management at around 0.2 percent of GDP. Of the total damage cost, about two thirds comes from damages to health, and a third from natural resource degradation. It should be noted that no cost estimate is provided for degradation associated with industrial, hazardous, and hospital waste, as sufficient data were unavailable. Similarly, cost assessment of degradation associated with inadequately treated wastewater is limited, due to data constraints. Cost is also presented for a limited number of remedial actions, in each of the environmental areas for which damage cost is estimated. More detailed analysis is required in future work, in order to compare benefits of remediation, to reduction in damage marginal cost.